REDUCING IMPRISONMENT RATES AND PREVENTION OF CRIMINALITY IN CONPEMPORARY GEORGIA - Aleksandre Glonti (European Scientific Journal, ESJ, 2012)
Combating to crime is a challenge for modern-day Georgia since the "Rose Revolution". Over the past 8 years the crimerate has decreased on average three times and also significantly reduced the level of population victimization. At thesame time, the number of people serving sentences in prison dramatically increased.According to statistical data in Georgia the number of prisoners per capita is one of the highest in the world which can beconsidered as a very negative factor for political image of country and requires serious reform of criminal legislation in orderto decriminalize the criminal violations that are not grave. The author of the article examines some of the offenses for whichlegislator should mitigate the sanctions excepting the deprivation of liberty.